Influence of different surface treatments of nickel chrome metal alloy and types of metal primer monomers on the tensile bond strength of a resin cement - Raghad S. Jamel; Màan M. Nayif; Mohammed A. Abdulla (Saudi Dental Journal)
Objective: To evaluate the effect of different surface treatments of nickel chrome (NiCr) with the type of metal primer monomers on the conventional tensile bond strength (CTBS) of resin cement. Methods: Forty disks of NiCr alloy were prepared for CTBS test and grouped as follows: group (1) no surface treatment (control group), group (2) oxide layer only, group (3) air abrasion, and group (4) air abrasion with an oxide layer. Each main group was subdivided into two subgroups (n = 5) depending upon the type of metal primer used for metal treatment. All specimens were bonded with resin cements. The CTBS was tested using a tensile testing machine. The data were statistically analyzed with One-way ANOVA, Two-way ANOVA, and T-test at 0.05 level of significance. Results: Significant differences in the mean value of the CTBS between different surface treatments (P ≤ 0.05) were observed. Tukey's test showed that air abrasion surface treatment had the highest mean value followed by the air abrasion with an oxide layer and oxide layer only. The control group showed the lowest value of significant difference compared to all treated groups (P ≤ 0.05). Conclusions: CTBS of self-adhesive resin cement to NiCr is dependent on surface treatment. Two types of the metal primer of different monomer contents 10-methacryloyloxydecyldihydrogenphosphate (MDP) or Thiophosphoricmethacrylate (MEPS) show similar behavior on the tensile bond strength. Keywords: Metal primer, Nickel chrome, Resin cement